2022
DOI: 10.4103/1735-5362.329930
|View full text |Cite
|
Sign up to set email alerts
|

Design, synthesis, and molecular docking of cysteine-based sulphonamide derivatives as antimicrobial agents

Abstract: Background and purpose: The preponderance of microbial infections remains a global challenge. In the present study, synthesis of novel cysteine-based antimicrobial agents and their biological evaluation is reported. Experimental approach: The reaction of p -toluenesulphonyl chloride with cysteine afforded 2-{[(4-methylphenyl)sulphonyl]amino}-3-sulphanylpropanoic acid (3) which was acetylated based on Lumiere-Barbier … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Their usual incorporation into a core ring structure gives them specific conformations which fit the active sites [ 79 ]. Sulfonyl group-containing compounds exhibit therapeutic effects against bacterial infections [ 80 , 81 , 82 , 83 , 84 , 85 , 86 ], tumors [ 87 , 88 ], Alzheimer’s disease [ 89 ], oxidative stress-related diseases [ 90 , 91 , 92 , 93 ], and diabetes [ 79 ]. Moreover, sulfonyl-containing compounds have been found to activate the Nrf2 pathway and inhibit Keap1–Nrf2 protein–protein interaction, thereby alleviating oxidative stress and inflammatory conditions [ 94 ].…”
Section: Nrf2-activating Synthetic Organosulfur Compoundsmentioning
confidence: 99%
“…Their usual incorporation into a core ring structure gives them specific conformations which fit the active sites [ 79 ]. Sulfonyl group-containing compounds exhibit therapeutic effects against bacterial infections [ 80 , 81 , 82 , 83 , 84 , 85 , 86 ], tumors [ 87 , 88 ], Alzheimer’s disease [ 89 ], oxidative stress-related diseases [ 90 , 91 , 92 , 93 ], and diabetes [ 79 ]. Moreover, sulfonyl-containing compounds have been found to activate the Nrf2 pathway and inhibit Keap1–Nrf2 protein–protein interaction, thereby alleviating oxidative stress and inflammatory conditions [ 94 ].…”
Section: Nrf2-activating Synthetic Organosulfur Compoundsmentioning
confidence: 99%
“…This property also makes α,β-unsaturated sulfonyls to act as powerful dienophiles [ 180 ]. Several sulfonyl-containing compounds exhibit significant antioxidant and anti-inflammatory activities [ 181 , 182 , 183 , 184 ]. α,β-unsaturated sulfonyls are notable building blocks in the synthesis of organic compounds [ 185 ].…”
Section: αβ-Unsaturated Sulfonylsmentioning
confidence: 99%
“…Finally, phosphoserine phosphatase (PSPH) breaks down phosphorine to produce serine (Nelson et al 2021 ). Serine exhibits significant antioxidant activities (Maralani et al 2012 ; Egbujor et al 2019 ). (Chen et al 2021 ) reported that serine supplementation could represent a nutritional strategy for improving skeletal muscle functions in doxorubicin-exposed patients.…”
Section: Introductionmentioning
confidence: 99%